0.16s-0.5(s-2)=22.5

Simple and best practice solution for 0.16s-0.5(s-2)=22.5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.16s-0.5(s-2)=22.5 equation:


Simplifying
0.16s + -0.5(s + -2) = 22.5

Reorder the terms:
0.16s + -0.5(-2 + s) = 22.5
0.16s + (-2 * -0.5 + s * -0.5) = 22.5
0.16s + (1 + -0.5s) = 22.5

Reorder the terms:
1 + 0.16s + -0.5s = 22.5

Combine like terms: 0.16s + -0.5s = -0.34s
1 + -0.34s = 22.5

Solving
1 + -0.34s = 22.5

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + -0.34s = 22.5 + -1

Combine like terms: 1 + -1 = 0
0 + -0.34s = 22.5 + -1
-0.34s = 22.5 + -1

Combine like terms: 22.5 + -1 = 21.5
-0.34s = 21.5

Divide each side by '-0.34'.
s = -63.23529412

Simplifying
s = -63.23529412

See similar equations:

| d=4-f+19 | | -8=6cx-5 | | 4x+x+-7= | | 1+3c=99 | | 3y+15=5y-9 | | n^3-3n^2-10n=0 | | 2(3z-2)-2(2-2z)=4 | | 21=n+51 | | 9t-15t=-8 | | x+7y+5-2y+3x= | | x*8-77=x*3-7 | | 6x-1=9x-9 | | 27+4y-6=14y-9-4y | | n=.33n+.5n+.11n+1 | | 0.2x+7=27 | | a+3b+5a-2+b= | | 3(x+5)-x=4x-(2x+5) | | 152-3x=24x+20 | | 5n^2-33n-14=0 | | 4z=1.8+3.4 | | 3x-2=5x-20 | | 4x+3=43 | | -5=-6w | | 3z=2.6+1.3 | | x*x+x+4=0 | | 13y+2=20y-5 | | 19-(2x-3)=2(x+3)+3 | | 2y-10=4y | | 1.33*-20=x | | 4y-3x=8 | | 9t+7=90 | | 6(x+2)+7= |

Equations solver categories